High‐Performance UV–Vis–NIR Phototransistors Based on Single‐Crystalline Organic Semiconductor–Gold Hybrid Nanomaterials. (29th December 2016) - Jung, Ji Hyung; Yoon, Min Ji; Lim, Ju Won; Lee, Yoon Ho; Lee, Kang Eun; Kim, Dong Ha; Oh, Joon Hak
Abstract : Hybrid materials in optoelectronic devices can generate new functionality or provide synergistic effects that enhance the properties of each component. Here, high‐performance phototransistors with broad spectral responsivity in UV–vis–near‐infrared (NIR) regions, using gold nanorods (Au NRs)‐decorated n‐type organic semiconductor and N, N ′‐bis(2‐phenylethyl)‐perylene‐3, 4:9, 10‐tetracarboxylic diimide (BPE‐PTCDI) nanowires (NWs) are reported. By way of the synergistic effect of the excellent photo‐conducting characteristics of single‐crystalline BPE‐PTCDI NW and the light scattering and localized surface plasmon resonances (LSPR) of Au NRs, the hybrid system provides new photo‐detectivity in the NIR spectral region. In the UV–vis region, hybrid nanomaterial‐based phototransistors exhibit significantly enhanced photo‐responsive properties with a photo‐responsivity ( R ) of 7.70 × 10 5 A W −1 and external quantum efficiency (EQE) of 1.42 × 10 8 % at the minimum light intensity of 2.5 µW cm −2, which are at least tenfold greater than those of pristine BPE‐PTCDI NW‐based ones and comparable to those of high‐performance inorganic material‐based devices. While a pristine BPE‐PTCDI NW‐based photodetector is insensitive to the NIR spectral region, the hybrid NW‐based phototransistor shows an R of 10.7 A W −1 and EQE of 1.35 × 10 3 % under 980 nm wavelength‐NIR illumination. This work demonstrates a viable approach to high‐performance photo‐detecting systems with broad spectral responsivity. Abstract : Optoelectrical performances of phototransistors based on gold nanorods‐decorated n‐type single‐crystalline organic semiconductor nanowires are reported. Owing to the synergy among the excellent photo‐conducting characteristics of organic nanowire, the scattering effect and localized surface plasmon resonances of gold nanorods, the hybrid system exhibits broad spectral responsivity with unprecedented performances that are comparable to those of inorganic materials‐based phototransistors.